A Critical Interpretation of Ethics in Research (AYUSHDHARA, 2023)
The moral standards that direct a person's behavior are known as ethics. Doing what is morally and legally correct in research is sometimes referred to as practicing research ethics. They are standards of behavior that set boundaries between what is morally correct and inappropriate. The article discusses the value of ethics in relation to organizing, carrying out, and disseminating research. Good Clinical Practice and several recommendations have been explored. The legal concerns that are pertinent to research procedures have been discussed in the essay. Researchers, ethics committees, and journal editors are just a few of the stakeholders who are very concerned about research misconduct and its consequences. The importance of research ethical awareness has been emphasized. Methodology: The material of research ethics has been collected from different, articles, authentic literatures, manuscripts, and authentic net sources, like NCBI, PubMed etc. Conclusion: For the researchers, a diligent mindset is crucial. To safeguard research participants from damage, it is crucial to uphold protocol compliance, informed consent processes, openness and integrity, confidentiality, and other standards.